Technology and Agribusiness. - Grimblatt, Victor (Tutorials in Circuits and Systems Ser., 2022)
This book discusses the major problems that agribusiness is facing and the differenttechnologies that can be applied to solve and improve such issues. Agribusiness covers different topics such as arable farming, dairy farming, fruits, vegetables, meat, etc. Each of these domains has different needs that can beaddressed through smart agriculture technologies such as circuits and systems.